Polycyclic aromatic hydrocarbon emission in powerful high-redshift radio galaxies - Rawlings, J.; Seymour, Nick; Page, M.; De Breuck, C.; Stern, D.; Symeonidis, M.; Appleton, P.; Dey, A.; Dickinson, M.; Huynh, M.; Le Floc'h, E.; Lehnert, M.; et al. (2013)
We present the mid-infrared (IR) spectra of seven of the most powerful radio-galaxies known to exist at 1.5 < z < 2.6. The radio emission of these sources is dominated by the AGN with 500 MHz luminosities in the range 1027.8–1029.1 W Hz−1. The AGN signature is clearly evident in the mid-IR spectra; however, we also detect polycyclic aromatic hydrocarbon emission, indicative of prodigious star formation at a rate of up to ∼1000 M⊙ yr−1. Interestingly, we observe no significant correlation between AGN power and star formation in the host galaxy. We also find most of these radio galaxies to have weak 9.7 μm silicate absorption features (τ9.7 μm < 0.8) which implies that their mid-IR obscuration is predominantly due to the dusty torus that surrounds the central engine, rather than the host galaxy. The tori are likely to have an inhomogeneous distribution with the obscuring structure consisting of individual clouds. We estimate that these radio galaxies have already formed the bulk of their stellar mass and appear to lie at a stage in their evolution where the obscured AGN dominates the energy output of the system but star formation is also prevalent.